Ações afirmativas: políticas de permanência para estudantes cotistas na Universidade Federal de São Carlos - Cavichiolo, Katia Silene (2019)
Affirmative actions have been implemented in public educational institutions as a way of trying to "compensate" a history of social inequalities in the access to Brazilian higher education. Among other public policies, vacancies in federal higher education institutions, implemented by Law 12.711 / 12, have expanded and diversified access to federal universities for the popular, black, brown and indigenous classes. However, student permanence at the university began to play a fundamental role for these actions to become effective. It is understood that affirmative action in higher education institutions involves the access and continuity of students from historically excluded groups. Two concepts are used as a key points: redistribution, which consists of the social policy of equality in terms of the distribution of political and economic resources represented not only by vaccancies to access the university, but also by the economical support of the quota students for their stay in the university; and recognition, understood as cultural politics of difference, that is, that institutionalized patterns allow parity among individuals, without one group being subordinate to the other. In this context, this masters dissertation objective to understand how and if affirmative actions, especially policies addressed to the student stay, have contributed to the inclusion of students historically excluded from educational degree, from a local reality. To explore this phenomenon, we chose a case study at the Federal University of São Carlos (UFSCar), São Carlos campus, Brazil. It was based on the triangulation of data searched by a literature review, analysis of 8 documents in the period 2014-2018 and thematic conversations, composed of a group activity and 7 interviews, among which 5 individual and 2 in double, all the participants entering in the university through the modalities of quotas, with registrations active in the face-to-face undergraduate courses. The results indicate the existence of institutional support in three dimensions: material, symbolic and pedagogical, which, according to the participants, are not enough for the inclusion of the poorest students in the University. From the perspective of the redistribution-recognition dilemma, it was found that the university invests in "affirmative remedies" that need retroalimentacion constantly, unlike the "transformative remedies" enable to emancipate groups. It is considered, therefore, that, despite the positive results in progress, some transformative initiatives could be adopted in order to broaden the scope of inclusion promoted by affirmative action at the university studied.